A practical and time-efficient high-intensity interval training program modifies cardio-metabolic risk factors in adults with risk factors for type ii diabetes - Phillips, Bethan E.; Kelly, Benjamin M.; Lilja, Mats; Ponce-González, Jesús Gustavo; Brogan, Robert J.; Morris, David L.; Gustafsson, Thomas; Kraus, William E.; Atherton, Philip J.; Vollaard, Niels B. J.; Rooyackers, Olav; Timmons, James A. (Frontiers Media, 2017)
Introduction: Regular physical activity (PA) can reduce the risk of developing type 2 diabetes, but adherence to time-orientated (150 min week−1 or more) PA guidelines is very poor. A practical and time-efficient PA regime that was equally efficacious at controlling risk factors for cardio-metabolic disease is one solution to this problem. Herein, we evaluate a new time-efficient and genuinely practical high-intensity interval training (HIT) protocol in men and women with pre-existing risk factors for type 2 diabetes.